2018
DOI: 10.3390/ma11050653
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Oxidation of Soot on a Novel Active Ca-Co Dually-Doped Lanthanum Tin Pyrochlore Oxide

Abstract: A novel active Ca-Co dually-doping pyrochlore oxide La2−xCaxSn2−yCoyO7 catalyst was synthesized by the sol-gel method for catalytic oxidation of soot particulates. The microstructure, atomic valence, reduction, and adsorption performance were investigated by X-ray powder diffraction (XRD), scanning electron microscope (SEM), Fourier-transform infrared spectroscopy (FT-IR), X-ray photoelectron spectroscopy (XPS), H2-TPR (temperature-programmed reduction), and in situ diffuse reflection infrared Fourier transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Zhu et al [20], confirmed that bridged bidentate nitrites were the main adsorbed species over CeO2 and transition-doped ceria (M0.1Ce0.9O2) catalysts, since the bridged bidentate nitrates were scarcely observed. Ait et al [21], also evidenced the formation of chelating nitrites, bidentate and monodentate nitrates on La2Sn2-yCoy catalyst. Bin et al [15], on the other hand, presented information not only of the type of nitrates formed in the catalyst surfaces but also on the soot particle surfaces, as evidence of the interaction of the three components of the system (soot/O2/NOx).…”
Section: Introductionmentioning
confidence: 91%
“…Zhu et al [20], confirmed that bridged bidentate nitrites were the main adsorbed species over CeO2 and transition-doped ceria (M0.1Ce0.9O2) catalysts, since the bridged bidentate nitrates were scarcely observed. Ait et al [21], also evidenced the formation of chelating nitrites, bidentate and monodentate nitrates on La2Sn2-yCoy catalyst. Bin et al [15], on the other hand, presented information not only of the type of nitrates formed in the catalyst surfaces but also on the soot particle surfaces, as evidence of the interaction of the three components of the system (soot/O2/NOx).…”
Section: Introductionmentioning
confidence: 91%
“…However, Mn15 catalyst showed a spherical shape nanoclusters structure. Small pores formed by the accumulation of elementary particles were observed on all oxides, which was in favor of the gaseous reaction in the catalytic process [38].…”
Section: Sem Analysismentioning
confidence: 96%
“…It is noticed that with increasing the concentration of La at the Ba site above x=0.04, a weak XRD peak belongs to phase La2Sn2O7 is appeared in XRD pattern. However, the vibrational band associated with La2Sn2O7 is observed within the wavenumber range 550 to 680 cm -1 [37]. So, the identification of the pyrochlore phase present in the sample can't be done using this analysis.…”
Section: Fourier Transform Infrared (Ftir) Spectroscopy Analysismentioning
confidence: 99%